(untitled) (Research, Society and Development, 2024)
COVID-19, initially identified in China, is a coronavirus causing systemic damage with a high potential for morbidity and mortality. Given the pandemic’s magnitude, societal changes are suggested, as observed in other historical catastrophes, particularly impacting health and birth rates. Thus, the objective of this study was to analyze birth rates in Fortaleza during the pandemic through socio-epidemiological profiles of women and pregnant individuals. It is an observational, retrospective, descriptive, quantitative study conducted with data from 2016 to 2021 obtained from Fortaleza’s SINASC. Between 2016 and 2019, a significant reduction (p<0.001) in the monthly average of live births in Fortaleza was observed compared to 2020 and 2021. Additionally, the group of neighborhoods classified with Very Low HDI was the only one that showed a significant increase in the average (p=0.02). The decrease in birth rates was consistent across all age groups, with a higher prevalence of children born to women with 8-11 years of education. Post-pandemic, there was a decline among younger women and an increase among those aged 35 to 44. Regarding prenatal visits, there was an absolute reduction, corresponding to the overall decrease in the number of births. Although many theories could explain the factors contributing to this outcome, such as increased symptoms of anxiety and depression, economic impact, and unemployment, new studies are necessary to elucidate the causes and consequences of the COVID-19 pandemic on a population’s birth rate.